The study of informational professional field of pharmacy specialists - N. O. Tkachenko (Zaporozhye State Medical University, 2014)
Today professionalism is important not only for the characteristics of an individual, but also for the manifestation of professional activities. Self-education, self-training and training on the working place are integral elements of the whole continuous professional development. Various components of professionalism form the social responsibility of pharmacist in contemporary conditions. During all professional activities of pharmacists the continuous formation of administrative, economic, legal, communication, social and information competence takes place. Professionally oriented periodical publications, scientific and practical activities act as assistants in it. The aim of this work was to study the sources of the information professional field of pharmaceutical establishments' staff in the South-eastern region of Ukraine and to determine the frequency of their use and orientation. Gathering of information was carried out using questionnaires. The structure of the developed questionnaire provided conventional separation of questions into two blocks. The first set of questions in the questionnaire provided respondents' characteristics by demographic and psychological criteria: age, position, length of service, type of enterprise's ownership. The second set of questions provided the opportunity to identify the main sources of professional information of the specialists in the region, the frequency of their use and the orientation of information for practical activities. Results and discussion. The respondents were proposed the list of periodicals, which today pharmacy specialists are guided by for understanding of modern trends in medicine and pharmacy. The survey results made it possible to determine the most required in practice, sources of information on modern medicine and pharmacy: special edition "Mister blister", "Weekly Drugstore" and "Pharmacist Practical worker". Experts of various levels of pharmacy management use these publications in print. The analysis of the nature of the information which the respondents are interested in showed that the information on new drugs and the issues of legislative and normative regulation of pharmaceutical enterprises' activities is the most studied. Unfortunately, quite a few practical workers are interested in issues of social direction, administration (management) in pharmacy and marketing activities. To the question «How often do you work with Proceedings of scientific practical conferences?" 60,3% of respondents answered that they study and work with them rarely and only in their spare time from work. Only 19,8% of respondents always learn and study the conference proceedings. Unfortunately, almost the same proportion of professionals (19,9%) are not interested or they are very rarely interested in proceedings of Scientific Practical Conferences, as they think the information of Conferences is only intended for scientists and managerial leaders. The positive result of the questionnaire was that 98% of respondents consider it necessary to conduct centralized measures on each enterprise concerning staff awareness of new trends in pharmaceutical science and practice of frequency once in half a year. That is the optimal frequency as it is believed by 63% of respondents. Conclusions. It was determined that very little attention is paid by the experts to the national scientific periodicals that are professional (magazine is included in the list of publications recognized by HAC of Ukraine). Almost half of the surveyed professionals rarely work with specialized publications, which are available in their companies. The disadvantage of the process of pharmacists' review with innovative search and achievements of scientists in the field of pharmacy is that only 20% of pharmacy specialists at various levels of management in the course of their practical activities work with the materials of scientific practical conferences. Such situation can be explained by the lack of motivation in self-education by specialists in the working hours. The problem revealed requires further research on defining factors of motivation for self education and improving their professionalism, which will be the next stage of our work.